A evolução do mercado de trabalho formal do profissional da informação no Brasil: um estudo a partir da RAIS/MTE, de 1985 a 2005 - Andre de Souza Pena (2007)
The dissertation presents a study on the evolution of the market of work of the professional of the information in Brazil. For in such a way, a descriptive survey is made with quantitative approach, of the data of the Annual Relation of Information Social (RAIS), of the Ministry of the Work and Job. The research if motivated from the necessity of if understanding the space where this professional occupies in the work market, in view of the new context of the call society of the information, where the advent of the new technologies of information modified the social relations, mainly, the ones that if they relate to the work, over all, to the work with information. The theoretical point of view it of the work was considered thematic and its development throughout century XX, with approach for the question of the productive reorganization in the decade of 1990. The contemplated period was of 1985 the 2005, with the objective to analyze the evolution of the market of work of the librarian, from the data of the RAIS. As delimitation of who is the professional of the information, used it definition of the Brazilian Classification of Occupations, version 2002, that it nominates the professional of the information as the bachelor in librarianship. It was argued, in this direction, the historical constitution of the librarianship, particularly in Brazil, with a boarding regarding the professional denomination of the information, the composition for sort of the category, beyond too much carried through studies already regarding the work market. The main results had been the prevalence of the professionals in the Southeastern region of Brazil, but with trend the growth of the number of professional is of the great capitals; the continuous growth of the number of professionals of the male sex was also observed, that in last the two years of the study had passed, proportionally, to better receive remuneration that the female librarians. The growth of the number of professionals in the segment of education and, particularly, the importance of the public institutions in the guarantee of job for the librarians was also evidenced. The research innovated for applying a evolution study of the market of work of the librarian from the RAIS, that is an official source of information come from the establishments employers. One expects with the present work to contribute to guide the librarianship schools, as well as the advice, associations and unions in its politics of formation and accompaniment of the work market.